The E/e’ Ratio—Role in Risk Stratification of Acute Heart Failure with Preserved Ejection Fraction - Marilena-Brîndușa Zamfirescu; Liviu-Nicolae Ghilencea; Mihaela-Roxana Popescu; Gabriel Cristian Bejan; Sean Martin Maher; Andreea-Catarina Popescu; Maria Dorobanțu (Medicina, 2021)
Background and Objectives: Heart failure with preserved ejection fraction (HFpEF) remains a worldwide management problem. Although there is a general effort for characterizing this population, few studies have assessed the predictive value of the echocardiographic E/e’ ratio in patients with acute HFpEF. The aim of the study was to identify groups with different prognosis in patients hospitalized with a first acute episode of HFpEF. Materials and Methods: The primary endpoint of the study was heart failure readmissions (HFR) at 6 months, while the secondary outcome was six-month mortality. We consecutively enrolled 91 patients hospitalized for the first time with acute HFpEF. We examined the E/e’ ratio as an independent predictor for HFR using univariate regression. Results: We identified and validated the E/e’ ratio as an independent predictor for HFR. An E/e’ ratio threshold value of 13.80 was calculated [(area under the receiver operating characteristic curve (AUROC) = 0.693, sensitivity = 78.60%, specificity = 55%, p < 0.004)] and validated as an inflection point for an increased number of HFR. Thus, we divided the study cohort into two groups: group 1 with an E/e’ ratio < 13.80 (n = 39) and group 2 with an E/e’ ratio > 13.80 (n = 49). Compared to group 1, group 2 had an increased number of HFR (p = 0.003) and a shorter time to first HFR (p = 0.002). However, this parameter did not influence all-cause mortality within six months (p = 0.84). Conclusions: The dimensionless E/e’ ratio is a useful discriminator between patients with acute HFpEF. An E/e’ value over 13.80 represents a simple, yet effective instrument for assessing the HFR risk. However, all-cause mortality at six months is not influenced by the E/e’ ratio.